Polemos come unità di guerra e pace. Una rilettura dei Saggi eretici sulla filosofia della storia di Jan Patočka - Barbieri, Marco (Filosofia, 2023)
Among the many philosophical contributions on war and peace written in the past century, the last of Jan Patočka’s six Heretical Essays in the Philosophy of History stands out as a particularly intense and enigmatic case. Aim of the present paper is to highlight Patočka’s peculiar account of the relationship between the two concepts, which defies common-sense expectations and argues for an alternative meaning of Polemos. In order to do so, the analysis also needs to carefully look at the five previous Heretical Essays, as well as referencing to the author’s other political writings. The paper therefore starts with a commentary on Wars of the Twentieth Century and the Twentieth Century as War, and then employs a backwards movement as a methodological tool to find the roots of Patočka’s articulation of war and peace in the other essays – revealing, once confronted with the ontological background of the passage from prehistory to history, significant intuitions for a constructive solution.